Factors limiting deceased organ donation: Focus groups' perspective from culturally diverse community - Wong, L.P. (Elsevier, 2010)
Background. In-depth understanding of cultural and religious factors limiting organ donation of three ethnic populations (Malay, Chinese, and Indian) in Southeast Asia is lacking. Identification of factors limiting organ donation among these three ethnic groups will provide insights into culturally appropriate strategies to promote acceptance of organ donation in a multiethnic Asian community. Methods. A total of 17 focus group discussions (105 participants) were conducted between September and December 2008. Participants were members of the general public aged 18 to 60 years, recruited through convenient sampling around the Klang Valley area of Malaysia. Results. Although the majority had favorable attitudes toward deceased organ donation and transplantation, a diversity of myths and misinformation were unearthed from the discussions across the ethnic groups. These include perceived religious prohibition, cultural myths and misperceptions, fear of disfigurement, fear of surgery, distrust of the medical system, and family disapproval. Culture and religious beliefs played important prohibitive roles among those opposed to organ donations. There were distinctive ethnic differences in cultural and religious concerns regarding organ donation. Less-educated and rural groups appeared to have more misconceptions than the well-educated and the urban groups. Conclusion. Our findings may assist organ donation and transplantation organizations to reach diverse sociodemographic and ethnic communities with culture-specific information about organ donation. The involvement of community and religious leaders is critical in organ donation requests.